Modeling and management of potential movement corridors for elk (cervus elaphus), bighorn sheep (ovis canadensis) and grizzly bear (ursus arctos) in the radium hot springs area, British Columbia - Tremblay, Marie A. (Environmental Design, 2001)
Bibliography: p. 292-307.